If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -1(-11) = -15 Multiply -1 * -11 y + 11 = -15 Reorder the terms: 11 + y = -15 Solving 11 + y = -15 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + y = -15 + -11 Combine like terms: 11 + -11 = 0 0 + y = -15 + -11 y = -15 + -11 Combine like terms: -15 + -11 = -26 y = -26 Simplifying y = -26
| 15-10y=21 | | -16=x-72 | | -1+m=16 | | 13y+22=16.6 | | m-13=-8 | | y+(-18)=-37 | | 3x-(2x-6)=2 | | 3x-10x+15=20 | | 6y+12=5y | | 4x+2=10x-12 | | 8(3m-7)=32 | | -n+5+3n=15 | | y^3+49y=0 | | 4+2X-12x=0 | | -4+-2x=-3x-12 | | 12-2(n-2)=-2 | | -2x+13=-5x+21 | | 2x-2x+4=0 | | -3x-2x=-4-12 | | 2x+10x=0 | | -7y+3=21 | | 2x-5x+4=0 | | 45=3x-36+30 | | -2(2+x)=3(-x-4) | | 2x-2x-8=0 | | Y-7=18 | | 5x-6-3x=10 | | x^2(4x-1)=y | | 8(2a+3)=16a+20 | | x^2(4x-1)=0 | | 47x-4(x+2)=13+2x | | 10y^2+19y+6= |